2018
DOI: 10.1038/s41598-018-35074-3
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and temporal distribution of the residual clusters of human leptospirosis in China, 2005–2016

Abstract: Human leptospirosis outbreaks still persistently occur in part of China, indicating that leptospirosis remains an important zoonotic disease in the country. Spatiotemporal pattern of the high-risk leptospirosis cluster and the key characteristics of high-risk areas for leptospirosis across the country are still poorly understood. Using spatial analytical approaches, we analyzed 8,158 human leptospirosis cases notified during 2005–2016 across China to explore the geographical distribution of leptospirosis hotsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
5
18
0
Order By: Relevance
“…The morbidity rate of leptospirosis is influenced by many factors, such as climate (temperature, humidity, rainfall, etc. ), carrier/reservoir populations (density, activity, abundance, amplifier host) and people (immunization coverage, effective antibody levels) (Dhewantara et al, ; Zhang, Wang, et al, ). Previous studies indicated that the morbidity of leptospirosis follows distinct seasonal patterns and is strongly associated with high rainfall amounts and flooding, when leptospires are widely dispersed in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The morbidity rate of leptospirosis is influenced by many factors, such as climate (temperature, humidity, rainfall, etc. ), carrier/reservoir populations (density, activity, abundance, amplifier host) and people (immunization coverage, effective antibody levels) (Dhewantara et al, ; Zhang, Wang, et al, ). Previous studies indicated that the morbidity of leptospirosis follows distinct seasonal patterns and is strongly associated with high rainfall amounts and flooding, when leptospires are widely dispersed in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a couple of studies have been conducted on the prevalence of leptospirosis infection in different animal species and humans in many regions of China (Dhewantara et al, ). The spread of leptospirosis among humans has the significant regional distribution, seasonal characteristic in China, while the leptospirosis infection also tracked closely with gender, age and occupation, while analysis is as follows: Leptospirosis is mainly transmitted by direct contact with infected/carrier animal hosts, exposure to urine from carriers or contact with water sources contaminated with carrier urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global or large scale gridded population datasets considered state-of-the-art in terms of open access archives of population distribution data include: the Rural-Urban Mapping Project (GRUMP) [5], the Gridded Population of the World, Version 4 (GPWv4) [6,7], the LandScan Global Population database [8,9], the Global Human Settlement Layer-Population grid (GHS-POP) [10,11], the WorldPop datasets [12][13][14][15][16] and the recently developed High Resolution Settlement Layer (HRSL) population grids [17]. Current and previous versions of these products have proved to be an important source of information and essential input for a wide range of cross-disciplinary applications including: poverty mapping [18][19][20], epidemiological modelling and disease burden estimation [21][22][23], interconnectivity and accessibility analyses [24][25][26], deriving past and future population estimates [15,27,28], disaster management [29][30][31] and human settlement characterisation [32] among others.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, by identifying super-susceptible locations, we aim finding the most susceptible nodes within the spatial human movement network. One similar concept in spatial analysis is the low-high outliers, that is any location with low density of disease cases which is surrounded by high density locations, thereby making it more vulnerable as it has a higher probability to report a higher number of cases in the following time period 54 . In the field of network science, the concepts of ‘spreaders’ and ‘receivers’ first appeared in the Hyperlink-Induced Topic Search (HITS) algorithm 22 as hubs and authorities, respectively.…”
Section: Introductionmentioning
confidence: 99%